To substitute \( x = 3 \) into the original equation \( 5(x + 2) = 2x + 19 \):
-
Substituting into the left side: \[ 5(3 + 2) = 5(5) = 25 \]
-
Substituting into the right side: \[ 2(3) + 19 = 6 + 19 = 25 \]
So, the equation becomes: \[ 5(5) = 25 \quad \text{and} \quad 2(3) + 19 = 25 \]
Both sides equal 25 when \( x = 3 \).
In summary:
- Left side: \( 5(3 + 2) = 25 \)
- Right side: \( 2(3) + 19 = 25 \)
Thus, the required substitutions are as follows:
-
For the left side with \( x = 3 \): \[ 5(3 + 2) = 25 \]
-
For the right side with \( x = 3 \): \[ 2(3) + 19 = 25 \]